2023
DOI: 10.5194/acp-23-12441-2023
|View full text |Cite
|
Sign up to set email alerts
|

Gas–particle partitioning of semivolatile organic compounds when wildfire smoke comes to town

Yutong Liang,
Rebecca A. Wernis,
Kasper Kristensen
et al.

Abstract: Abstract. Wildfires have become an increasingly important source of organic gases and particulate matter in the western USA. A large fraction of organic particulate matter emitted in wildfires is semivolatile, and the oxidation of organic gases in smoke can form lower-volatility products that then condense on smoke particulates. In this research, we measured the gas- and particle-phase concentrations of semivolatile organic compounds (SVOCs) during the 2017 northern California wildfires in a downwind urban are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 73 publications
1
2
0
Order By: Relevance
“…Based on these observations, it is reasonable to assume that these compounds will remain particle-bound throughout their atmospheric lifetime, even in aqueous solution. Indeed, this is consistent with observations of wildfire smoke particles that show 4NC is primarily particle bound even when aerosol mass concentrations are low following plume dilution . This also indicates favorable gas-to-particle partitioning of compounds with similar volatility in the BB plume.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Based on these observations, it is reasonable to assume that these compounds will remain particle-bound throughout their atmospheric lifetime, even in aqueous solution. Indeed, this is consistent with observations of wildfire smoke particles that show 4NC is primarily particle bound even when aerosol mass concentrations are low following plume dilution . This also indicates favorable gas-to-particle partitioning of compounds with similar volatility in the BB plume.…”
Section: Resultssupporting
confidence: 89%
“…Indeed, this is consistent with observations of wildfire smoke particles that show 4NC is primarily particle bound even when aerosol mass concentrations are low following plume dilution. 54 This also indicates favorable gas-to-particle partitioning of compounds with similar volatility in the BB plume.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…However, the gas-phase C 6 H 10 O 5 is not expected to be the most abundant species from fresh crop straw and wood burning emissions in this study, attributing to the fact that C 6 H 12 O 5 is more enriched in the particle phase rather than the gas phase due to fast gas-particle partitioning. Consistently, Liang et al (2023) evaluated the phase partitioning behaviors of biomass burning markers and found that levoglucosan, mannosan and nitrocatechols mainly stay in the particle phase.…”
Section: 1029/2023jd040568mentioning
confidence: 85%